The ladder of competitiveness : how to climb it - Causa, Orsetta; Cohen, Daniel; Organisation for Economic Co-operation and Development (Paris : OECD, 2006)
Tables of national competitiveness give an easily comparable ranking of the winners and losers of global economic competition, but they do not explain why the poor countries are four times less productive than the rich ones or why some rich countries are twice as productive as others. Using empirical data from over 50 countries, this book shows how even small differences in a number of factors combine to boost or block productivity. Governments need such information to set priorities. Investors need it too, and two new rankings are proposed as alternatives to a simple comparison of industrial productivity. The first, called the investor ranking, is based on infrastructure, human capital and total factor productivity. The second, exporter ranking, is for investors whose prime concern is for a production platform well-integrated into world trade. Combining the new rankings with a more traditional one produces three groups of countries, termed balanced, high potential, and vulnerable. Group membership reserves some surprises: you may be rich, but that does not mean you are not vulnerable.--Publisher's description
Manufacturing productivity -- Explanatory factors -- The overall productivity of the economy -- Social infrastructure -- International trade -- New approaches to competitiveness
Includes bibliographical references (p.129-137)
Keywords: Industrial productivity; Competition